Cyclodextrin-Based Nanosponges -A Promising Nano technological Drug Delivery System - Hassanien Sagban Taghi (Journal of Global Pharma Technology, 2016)
Undoubtedly, Cyclodextrin-based nanosponges (CD-NSs) are patentable nanosized, efficient delivery system designated as a three-dimensional nanostructure network. It can form porous spherical nanoparticles with a crystalline or amorphous structure. The internal polarizability of NS can be easily adjusting by alternating the type of cross-linker (CL) molecules and degree of cross-linking. Cyclodextrin-based nanosponges are a safe and can form complexes with different types of lipophilic or hydrophilic molecules. The nanosponges could be used to improve the aqueous solubility of poorly water-soluble molecules, protect degradable substances, obtain sustained delivery systems or design innovative drug carriers for nanomedicine.Keywords: Cyclodextrin, Nanosponges, Drug Delivery System.